A comprehensive survey of the grapevine VQ gene family and its transcriptional correlation with WRKY proteins - Wang, Min; Vannozzi, Alessandro; Wang, Gang; Zhong, Yan; Corso, Massimiliano; Cavallini, Erika; Cheng, Zong-Ming (Max) (Frontiers in Plant Science, 2015)
WRKY proteins are a class of transcription factors (TFs) involved in the regulation of various physiological processes, including the plant response to biotic and abiotic stresses. Recent studies in Arabidopsis have revealed that some WRKY TFs interact with a class of proteins designed as VQ proteins because of their typical conserved motif (FxxxVQxLTG). So far, no information is available about the genomic organization and the function of VQ motif-containing protein in grapevine (Vitis vinifera L). In the current study, we analysed the 12X V1 prediction of the nearly homozygous V. vinifera PN40024 genotype identifying up to 18 predicted VQ genes (VvVQ). VvVQs phylogenetic and bioinformatic analyses indicated that the intron-exon structures and motif distribution are highly divergent between different members of the grapevine VQ family. Moreover the analysis of the V. vinifera cv. Corvina expression atlas revealed a tissue- and stage- specific expression of several members of the family which also showed a significant correlation with WRKY TFs. Grapevine VQ genes also exhibited altered expression in response to drought, powdery mildew infection, salicylic acid (SA) and ethylene (ET) treatments. The present study represent the first characterization of VQ genes in a grapevine genotype and it is a pivotal foundation for further studies aimed at functionally characterizing this mostly unknown grapevine multigenic family.